Welcome back survey: exploring concerns impacting HIV care engagement and retention. Issue 9 (1st September 2016) - Gonzalez, Marisol; Precht, Allison; Fletcher, Jason; Catrambone, Jennifer; Bailey, L'Oreal; Espino, Susan Ryerson
ABSTRACT: The current study describes the development of a short pre-clinic survey that helped multidiscipline providers to elicit patient perspective on barriers to HIV primary care. The survey was piloted with 318 patients returning to care after being lost to care for at least 12 months. Reasons for breaks in care were dependent on age, gender, and race. Concerns about confidentiality in care were more commonly reported by African-American, Latino, and younger patients, while concerns relating to acceptance of diagnosis and side effects were greater for women, African-American, and Latino participants. Further, Intimate Partner Violence (IPV) and transportation were greater concerns for women and younger patients in the sample.